Prévalence of Helicobacter pylori infection and gastric preneoplastic lesions in patients admitted for upper gastro-intestinal endoscopy in Cotonou (Benin Republic). - Kpossou, A.R. (My University, 2020)
Infection with Helicobacter pylori (H. pylori) is common in developing countries such as Benin. This germ can cause several gastroduodenal diseases such as gastritis, ulcer, adenocarcinoma or gastric MALT lymphoma. This study aimed to determine the prevalence of H. pylori infection and gastric pre-neoplastic histological lesions in patients admitted for upper gastrointestinal endoscopy (UGE) and to identify factors associated with this infection. Methods: This was a cross-sectional descriptive and analytical study, with prospective data collection, conducted from October 2014 to December 2015. We included all patients admitted to Menontin Hospital for UGE in whom a gastric biopsy has been done. H. pylori research was conducted in anatomy-pathology, either in a medical laboratory in Cotonou or at the CERBA laboratory in Paris, France, depending on the patient's choice. The microscopic study was carried out after staining with Haematoxyline-Eosine-Safran (HES) and the search for H. pylori using Giemsa staining. Results: H. pylori was investigated in 137 patients, 67 men (48.9 %) and 70 women (51.1 %). The mean age was 48.3 ± 14.6 years with extremes of 10 and 83 years. Some patients had had at least one previous H. pylori eradication treatment (63 cases or 46 %). For the general population, the test was positive in 98 cases, i.e. a prevalence of 71.5 %. Depending on whether or not patients had been pre-treated for H. pylori, the test was positive in 40 out of 63 (63.5 %) pre-treated patients, versus 58 out of 74 (78.4 %) patients who were naïve to any eradication treatment (p = 0.057). The pre-neoplastic lesions noted were gastric atrophy in 35 patients (including 25 H. pylori positive), intestinal metaplasia in 13 patients (including 10 H. pylori positive) and low grade dysplasia in 14 patients (including 12 H. pylori positive); high grade dysplasia was found in one patient who was H. pylori negative. Only the type of prior eradicant treatment appeared to be associated with H. pylori infection (p=0.182). Conclusion: H. pylori infection is common in our patients admitted for upper gastrointestinal endoscopy. Gastric atrophy was the most common pre-neoplastic lesion.
Keywords: Helicobacter pylori; upper gastrointestinal endoscopy; gastric preneoplastic lesions; Cotonou